2010
DOI: 10.1111/j.1465-3362.2009.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

University faculty perceptions of the health risks related to cigarettes and smokeless tobacco

Abstract: This study found that the risks of ST use are overestimated and conflated to that of cigarettes among highly educated professionals, demonstrating the need for better education about the risks of tobacco use and for communication of accurate information by health organisations and agencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
2
23
1
Order By: Relevance
“…i As shown in table 2, measures of RRPs were highly variable and exhibited many characteristics. Although a majority of measures (n=41) operationalised risk as an overall concept of harm,22 and 23 24A 24B 27–30 31b 32 35 37 39 40 42a 43–46 50 51a 51b 52 54 57–63 65–73 75–76 some were based on distinct dimensions of risk,77 such as perceived severity,20 and 21 41 55 64 perceived susceptibility,29 31a 33–34 36 38 42b 47–49 53 55–56 64 74 and perceived likelihood 20 . and 21 In addition, several used aids to help guide respondents, such as an awareness prompt (n=9),22 and 23 30 24A 24B 49 50 54 56 58 or visual aids, such as product images (n=2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…i As shown in table 2, measures of RRPs were highly variable and exhibited many characteristics. Although a majority of measures (n=41) operationalised risk as an overall concept of harm,22 and 23 24A 24B 27–30 31b 32 35 37 39 40 42a 43–46 50 51a 51b 52 54 57–63 65–73 75–76 some were based on distinct dimensions of risk,77 such as perceived severity,20 and 21 41 55 64 perceived susceptibility,29 31a 33–34 36 38 42b 47–49 53 55–56 64 74 and perceived likelihood 20 . and 21 In addition, several used aids to help guide respondents, such as an awareness prompt (n=9),22 and 23 30 24A 24B 49 50 54 56 58 or visual aids, such as product images (n=2).…”
Section: Resultsmentioning
confidence: 99%
“…A majority of measures were direct in nature (n=50),20 and 21 , 22 and 23 24A 24B 28–30 31a 31b 32–33 35 37–40 42a 42b 43–50 51a 52–63 65–68 70–76 requiring respondents to make a direct comparison of the products, whereas seven measures were indirect,27 34 36 41 51b 64 69 in which the responses to separate questions were compared. Among the direct measures (n=50), question stems were either open (n=36),20 and 21 , 22 and 23 24A 24B 28–30 31a 32–33 35 39–40 43–49 51a 52–61 63 65 67 71 72 or closed (n=14) 31b 37–38 42a 42b 50 62 66 68 70 73–76.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In July 2011, The RJ Reynolds Tobacco Company submitted a citizen petition to the US Food and Drug Administration requesting that it change one of the smokeless tobacco warning labels from “WARNING: This product is not a safe alternative to cigarettes” to “WARNING: No tobacco product is safe, but this product presents substantially lower risks to health than cigarettes.” 1 This request referred to studies 27 reporting that a large portion of the public perceives smokeless tobacco products to be as harmful as or more harmful than cigarettes.…”
mentioning
confidence: 99%
“…Smokers greatly overestimate the risks of using pharmaceutical nicotine and smokeless tobacco (SLT) and underestimate the risks of 'light' or 'low tar' cigarettes [1][2][3][4][5][6][7].These misconceptions of risk have also been reported among highly educated samples, such as nurses [8] and university students and faculty [9,10], as is shown in the study by Peiper et al reported in this issue of the journal.The fact that well-educated health professionals are little better informed about the comparative risks of smoked and smokeless tobacco products indicates the need for public education. Some public health professionals oppose this on paternalistic grounds that have been well criticised by Kozlowski [11].…”
mentioning
confidence: 95%